FEATURES OF POSTDEGREE EDUCATION OF OBSTETRICIANS-GYNAECOLOGISTS IN MASTERING OF ENDOSCOPIC METHODS - N. V. Avramenko; D. E. Barkovsky; О. А. Nikiforov (Zaporožskij Medicinskij Žurnal)
In the article attention is accented on expediency of creation of thematic improvement cycle «Endoscopy in gynecology» for postdegree education of obstetricians-gynaecologists. There are basic components of curriculum and structure of cycle, and also thematic plans of lectures, practical and seminar classes. Purpose of cycle – is to teach a doctor obstetrician-gynaecologist for diagnostic hysteroscopy and laparoscopy performance, carrying out of basic endoscopic operations in gynecology. Task of cycle «Endoscopy in gynaecology» – to receive theoretical knowledge on bases of endoscopic gynaecology, on bases of it to carry out differential diagnosis and choose optimal tactics of operative intervention with endoscopic technique.